Expression of Intragenic LCAL4 Long Non-Coding RNAs as a Potential Diagnostic and Prognostic Marker in Female Breast Cancer - Maryam Behyari; Mahla Behyari (Tehran University of Medical Sciences, 2024)
Objective: In breast cancer early detection is associated with reduced mortality and it is essential to identify new biomarkers for early detection and appropriate management of cancer patients with the best response to treatment. Long non-coding RNAs (LncRNAs) have attracted much attention as potential diagnostic, prognostic, or predictive biomarkers due to their high specificity, easy access to non-invasive methods, and their aberrant expression under various pathological and physiological conditions. Have attracted the aim of this study is to investigate the expression profile of intragenic non-coding LncRNAs LCAL4 as a biomarker as potential diagnostic and prognostic biomarkers in cancer. Materials and methods: In this research, 62 tissue samples were obtained from patients undergoing therapeutic surgery in Khatam al-Anbia Hospital and the normal peripheral tissue that was removed for prevention was used as a control by Real-time PCR method. Results: The expression pattern of LCAL4 long non-coding RNA gene is significantly different between two groups of healthy control samples and samples obtained from patients with different breast cancer subtypes, Also its expression between samples obtained from different subgroups and different stages showed significant differences. Conclusion: The studied LncRNAs can act as a factor to identify tumor tissue from healthy tissue, and the diagnosis of cancer grades can be different depending on the type of LncRNA. These results can be proposed in the introduction of LncRNA LCAL4 as a new marker in the diagnosis of breast cancer. In addition, by interpreting the results, it can be concluded that these LncRNAs can be considered as influential factors in the process of breast cancer.